Taking the Wheel. Women and the Coming of the Motor Age - Larsen, Anne Trine (Kvinder, Køn & Forskning, 2004)
Anne Trine Larsen anmelder "Taking the Wheel. Women and the Coming of the Motor Age" af Virginia Scharff.